Plastics handbook (McGraw-Hill, 1994)
This handbook provides a complete guide to plastics processing materials, equipment and design. These articles from "Modern Plastics" provide information on resins and compounds, from ABS to vinylidene chloride; chemicals and additives; antifogging agents and UV stabilizers; reinforced plastics and composites, from aramid hybrids to thick moulding compound; primary processing, from blow moulding to thermoplastic structural foam moulding; auxiliary equipment and components; and fabricating and finishing. Technical enough to answer questions an engineer might have, the text remains readable for the inexperienced engineer in mechanical, design, materials or manufacturing engineering.